Diastema closure by direct technique in composite resin - a case report (Research, Society and Development, 2021)
Objective: The objective of this work is to report a clinical case of diastema closure using the direct resin technique guided by diagnostic waxing. Methodology: Based on the patient's permission through the Free and Informed Consent Term to share their image for the proper purpose, this study is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case Report: Female patient, 21 years old, brown, attended the dental clinic of CEUNI-Centro Universitário Fametro. In the anamnesis, she showed dissatisfaction with the aesthetics of the smile. During clinical examination, the presence of diastemas involving the region of the upper central and lateral incisors was observed. Final Considerations: Aesthetic rehabilitation through the direct technique in composite resin is an excellent alternative for closing diastemas, as long as it is done correctly, taking into account the operator's skill and the patient's cooperation after the treatment.